BIOLOGICAL SYNTHESIS OF Fe₂O₃ NANOPARTICLES: STRUCTURAL ANALYSIS AND ANTIMICROBIAL POTENTIAL - A.R. Bhosale; R.B.Chavan; A.A. Surwase; P.V. Chavan (The Bioscan, 2025)
This research examines the biological synthesis of Fe₂O₃ nanoparticles (NPs). The synthesis of Fe2O3 nanoparticles was carried out using saussurea obvallata pant extract, employing biological approach while following the conventional co-precipitation method. The synthesized Fe₂O₃ nanoparticles' structural and morphological characteristics were examined utilizing Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), and Transmission electron microscopy (TEM),Ultraviolet spectroscopy (UV).The antibacterial activity of the biogenically synthesized Fe₂O₃ NPs was also evaluated, demonstrating excellent antimicrobial efficiency in response to both Gram-positive and Gram-negative bacteria. The synthesized nanomaterials was exhibited excellent antimicrobial activity against bacterial strains Staphylococcus aureus (NCIM-2654), Bacillus cereus (NCIM-2703), Pseudomonas aeruginosa (NCIM-5032) and Proteus vulgaris (NCIM-2813). This study highlights the potential of plant-mediated green synthesis as an eco-friendly and sustainable approach for fabricating Fe₂O₃ NPs with promising biomedical applications.